Evaluation of Drug-Related Risk Behaviors Among Females Diagnosed With Early Syphilis in New York State (Excluding New York City), 2013 to 2018. (August 2021) - Drame, Fanta; Bomma, Srikanth; Miranda, Wilson; Gelberg, Kitty; Hart-Malloy, Rachel
Abstract : Abstract: This evaluation describes an increase in reported drug-related risk behaviors among females who are diagnosed with early syphilis over a 5-year span in New York State, excluding New York City. Integrating sexually transmitted infection prevention efforts with harm reduction services may help decrease syphilis rates in areas where drug-related risk behavior rates are high. Abstract : More than 30% of females diagnosed with early syphilis in New York State, excluding New York City, reported drug-related risk behaviors.